Prenatal ultrasound screening for congenital heart defects: current and future strategies. (November 2012) - Martínez-Moratalla, José Manuel; Escribano, David; Gómez-Montes, Enery; Herraiz, Ignacio; Galindo, Alberto
Congenital heart defects (CHDs) affect approximately three to eight out of 1000 live births and are a leading cause of fetal and postnatal mortality. Over the past 30 years, fetal echocardiography has emerged as an accurate tool to diagnose CHDs, and high-experience groups dealing with high-risk patients currently report detection rates of approximately 80–90% for major defects. However, the performance of obstetric ultrasound applied to the general obstetric population is still discouraging, with detection rates of 30–40% of major CHDs. Therefore, it is necessary to improve the results of obstetric ultrasound screening for CHDs. In this article, the authors describe current and future strategies that may be helpful, such as the uniform application of published guidelines for performing the so-called basic and extended-basic cardiac scan through comprehensive training, the implementation of new indications for performing fetal echocardiography and the use of new technologies such as 3D–4D scanning or telemedicine–internet remote consultation.